Does the size matter? Evaluation of effect of incorporation of silver nanoparticles of varying particle size on the antimicrobial activity and properties of irreversible hydrocolloid impression material. Issue 7 (July 2018) - Ginjupalli, Kishore; Shaw, Tushar; Tellapragada, Chaitanya; Alla, Ramakrishna; Gupta, Lokendra; Perampalli, Nagaraja Upadhya
Highlights: Conventional irreversible hydrocolloids do not have antimicrobial activity. Silver nanoparticles imparted antimicrobial activity to irreversible hydrocolloid. Silver nanoparticles of 80–100 nm were found to be superior than finer size range. Abstract: Objectives: The main objective of the present in vitro study is to evaluate the antimicrobial activity and properties of irreversible hydrocolloid impression material incorporated with silver nanoparticles of varying size at different concentrations. Methods: Silver nanoparticles of 80–100, 50–80, 30–50 and 10–20 nm size were added to irreversible hydrocolloid impression material at 0.5, 1.0, 2.0 and 5.0 wt%. Antimicrobial activity of the silver nanoparticle incorporated irreversible hydrocolloid was measured using disk diffusion method. The gel strength, flow, gelation time and permanent deformation were measured according to American Dental Association specification #18. Data were analyzed using analysis of variation at a confidence interval of 95% ( α  = 0.05). Results: Silver nanoparticles of 80–100 nm size have imparted superior antimicrobial activity to the irreversible hydrocolloid in a dose-dependent manner whereas finer nanoparticle size did not exhibit any antimicrobial activity. The addition of silver nanoparticles did not alter the properties of irreversible hydrocolloid at 0.5 and 1.0 wt% whereas at higher concentrations significant differences in flow, gelation time and strength were observed. Significance: The results of the present study indicate that silver nanoparticles of size range 80–100 nm are superior in imparting antimicrobial activity to irreversible hydrocolloid compared to finer particle size range.